Antimicrobial resistance of Escherichia coli isolated of ulam from supermarkets and wet markets in Kuala Terengganu, Malaysia - Anis Athirah Bahri; Wahida Salleh; Mohd Nizam Lani; Wan Zawiah Wan Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Raw vegetables were highly exposed to microbial contamination by handling at harvest or during postharvest processing. Nowadays, emerging issues threatening public health are bacterial resistance to antibiotics due to the excessive usage and misuse of antibiotics in agriculture. In this study, antibiotic susceptibility profiles of 23 Escherichia coli strains were tested by the standard disk diffusion method. Sixteen antimicrobial agents namely amikacin, amoxycillin/cluvanic acid, ampicillin, ampicillin/sulbactam, chloramphenicol, ceftriaxone, ciproflaxacin, ceftazidime, cephalotin, cefoperazone, gentamicin, kanamycin, nalidixic acid, streptomycin, tetracycline and trimethoprim were included in this study. In this study, 78.3% of the E. coli isolates were found to be resistant to cephalotin and it was the highest compared with the other antibiotics. It was found that 87% of isolates exhibited resistance to at least one antibiotic. E. coli showed high resistance to ampicillin (52.2%) and tetracycline (52.2%). In contrast, ceftriaxone and ceftazidime were found to be (100%) effective in restraining the growth of E. coli isolates. The highest multiple antibiotic resistance index (MAR) index was 0.48. Multiple resistance was observed in 47.8% of isolates with resistance to three to seven antibiotics. In conclusion, ulam could be the potential source of this antibiotic resistance of E. coli, and it may pose health threats to consumers.